Directed Expected Utility Networks - Leonelli, Manuele; Smith, Jim (Informs, 2017)
A variety of statistical graphical models have been deﬁned to represent the con-ditional independences underlying a random vector of interest. Similarly, many diﬀerentgraphs embedding various types of preferential independences, such as, for example, con-ditional utility independence and generalized additive independence, have more recentlystarted to appear. In this paper, we deﬁne a new graphical model, called a directedexpected utility network, whose edges depict both probabilistic and utility conditionalindependences. These embed a very ﬂexible class of utility models, much larger thanthose usually conceived in standard inﬂuence diagrams. Our graphical representation andvarious transformations of the original graph into a tree structure are then used to guidefast routines for the computation of a decision problem’s expected utilities. We show thatour routines generalize those usually utilized in standard inﬂuence diagrams’ evalua-tions under much more restrictive conditions. We then proceed with the construction of adirected expected utility network to support decision makers in the domain of householdfood security.
Keywords: 33 Ciencias Tecnológicas::3306 Ingeniería y tecnología eléctricas; ODS 2 - Hambre cero